Dampak Pengembangan Objek Wisata Pantai Tiram Terhadap Perekonomian Masyarakat - syafarini, saharisyah; Adnan, M Fachri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This study aims to see the extent to which the impact of the development of oyster beach tourism objects on the economy of the Tapakis village community carried out by the tourism and sports office of Padang Pariaman district and to find out what are the obstacles that occur when developing oyster beach tourism. This research is based on the existence of problems in the tourism object of the Tapakis oyster beach such as development that has not been maximized and tourist facilities that are not well managed. This research uses qualitative research using descriptive methods. The informants in this study in this study, namely the Tourism Development Sector, the Promotion and Creative Economy Sector, the Wali Nagari Tapakis, the Tourism Awareness Group and Community Figures.The data of this research are primary data and secondary data. Data collection techniques are carried out by means of interviews and documentation studies, as well as testing the validity of the data by using triangulation techniques and using reference materials. The data analysis technique in this study was carried out by summarizing the records that were found in the field and assisted by data collection tools such as cellphone recorders with informants while in the field, after which a conclusion was obtained. The results of this study indicate that the impact of the development of oyster beach tourism objects on the economy the community of Tapakis village, Padang Pariaman district. The youth tourism and sports office as well as Pokdarwis members have carried out promotions such as placing advertisements, billboards, magazines, newspapers, browsers, Facebook and Instagram. Currently, the facilities at Oyster Beach are adequate, but these facilities have not been well managed at this time and from an environmental perspective it is still not clean enough. the level of visits to tourist objects has started to increase now compared to previous years as well as the economic income of the people around oyster beach tourism has started to improve as well today.